Seedborne fungi on stored onion seeds - Medić-Pap Slađana S.; Tančić-Živanov Sonja Lj.; Danojević Dario Đ.; Ignjatov Maja V.; Ilić Aleksandra D.; Glogovac Svetlana K.; Gvozdanović-Varga Jelica M. (Zbornik Matice Srpske za Prirodne Nauke, 2022)
Seed as a highly-valuable resource is preserved in collections for many years. Although the seed is kept under optimal conditions, monitoring of germination and the presence of fungi during seed preservation is of great importance. Therefore the aim of this paper is to examine the seed health status and germination of 43 onion accessions kept in the timespan for 15 years in the Institute of Field and Vegetable Crops collection. Germination of seed samples varied from 7-93%. The presence of fungi in the collection was determined on 33 tested samples. Fungi from the genera Acremonium, Alternaria, Aspergillus, Cladosporium, Epicoccum, Fusarium and Penicillium were developed. The following Fusarium species identified on the seeds were F. proliferatum, F. graminearum, F. sporotrichioides, F. solani, F. pseudograminearum and F. equiseti. Based on factor analysis, Fusarium and Penicillium affected germination, while the occurrence of Alternaria species on onion seed is connected to the year of harvest.